Blasting in mines : new trends : workshop hosted by Fragblast 10 : the 10th International Symposium on Rock Fragmentation by Blasting, New Delhi, India, 24-25 November, 2012 - Ghose, Ajoy K.; Joshi, Akhilesh (CRC Press, 2013)
Blasting practices in mines have undergone many changes in the recent past and continue to be honed and reconfigured to meet the demands of today's mining needs. This volume compiles papers of the workshop Blasting in Mines - New Trends, hosted by the Fragblast 10 Symposium . The 17 papers provide a mix which highlight the evolving trends in blasting in mines. These range from special techniques of cast blasting, applications of seed wave modelling for improved fragmentation, to design of mass blasts and controlled blasting for stability of pit-walls. Blasting in Mines - New Trend.
"A Balkema book."
Keywords: Blasting -- Congresses.; Mining engineering -- Congresses.; elektronické knihy; electronic books